Conferring of drought tolerance in wheat (Triticum aestivum L.) genotypes using seedling indices - Ahmed, Hafiz Ghulam Muhu-Din; Zeng, Yawen; Shah, Adnan Noor; Yar, Muhammad Majid; Ullah, Aziz; Ali, Muhammad (Frontiers in Plant Science, 2022)
Wheat is the most widely grown and consumed crop because of its economic and social benefits. This crop is more important globally for food and feed, and its productivity is particularly vulnerable to abiotic factors. In this study, 40 wheat genotypes were studied to access the drought tolerance level using completely randomized design (CRD) in 250 ml disposable cups through morpho–physiological attributes at seedling stage. The wheat germplasm was tested under normal and two drought stress level D1 (50% field capacity) and D2 (75% field capacity) for different seedling attributes such as germination percentage (GP), chlorophyll content (CC), shoot length (SL), root length (RL), shoot fresh weight (SFW), root fresh weight (RFW), seedling fresh weight (SDFW), shoot dry weight (SDW), root dry weight (RDW), relative water content (RWC), root/shoot ratio (RS), and seedling dry weight (SeDW). The results of analysis of variance (ANOVA) and spider analysis indicate that significant amount of genetic variation was present and behavior of studied germplasm showed different behavior in different environment. The correlation analysis showed that root length has significantly positive association with root/shoot ratio, dry weight, and fresh weight while negatively correlated with shoot length and relative water content. Based on the positively associated traits, the studied genetic material would improve genetic gain for drought tolerance. The multivariate analysis showed that out 13 principal components only five PCs were significant and has eigenvalue > 1, cumulatively showed 82.33, 83.07, and 97.34% of total variation under normal, D1 and D2 conditions, respectively. Significantly, the result of spider graph and multivariate analysis showed that genotypes G47, G48, G65, G68, and G80 performed well in all drought stress conditions and considered as drought-tolerant genotypes. The best performing genotypes can be used in future breeding programs. The selection on the bases of studied attributes is effective for development of drought-tolerant and high-yielding varieties for sustainable food security.